Multilevel Analysis of Determinants of Stunting Prevalence among Children under Age Five in Ethiopia - Bayleyegne, Yenefenta Wube (International Journal of Child Health and Nutrition, 2021)
Background: Stunting is a well-established child health indicator of chronic malnutrition related to environmental and socio-economic circumstances. In Ethiopia, childhood stunting is the most widely prevalent among children under the age of five years. Objective: To estimate the prevalence of stunting and model the determinants of stunting prevalence among children under age five in Ethiopia. Methods: Data were extracted from 2016 EDHS, and samples of 8487 children under age five were used in this study. The sample was selected using a two-stage stratified sampling process, and a multilevel logistic regression model was used to determine the factors associated with childhood stunting in Ethiopia. Results: This study revealed that the prevalence of stunting among children under age five years in Ethiopia was around 39.39%. The multilevel binary logistic regression analysis was performed to investigate the variation of predictor variables of stunting prevalence among children under age five. Accordingly, it has been identified that the ages of the child above 12 months, male gender, children from poor households, and no mother education significantly affect the prevalence of stunting in Ethiopia. It is found that variances related to the random term were statistically significant, implying a variation in the prevalence of stunting across Ethiopia's regional states. Conclusion: The current study confirmed that the prevalence of stunting among children under aged five years in Ethiopia was a severe public health problem. Therefore, governmental or stakeholders should pay attention to all the significant factors mentioned in this study's analysis.